2009
DOI: 10.1016/j.cub.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Evolution by Genomic Island Transfer Occurs via DNA Transformation In Planta

Abstract: Our understanding of the evolution of microbial pathogens has been advanced by the discovery of "islands" of DNA that differ from core genomes and contain determinants of virulence. The acquisition of genomic islands (GIs) by horizontal gene transfer (HGT) is thought to have played a major role in microbial evolution. There are, however, few practical demonstrations of the acquisition of genes that control virulence, and, significantly, all have been achieved outside the animal or plant host. Loss of a GI from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 23 publications
2
54
1
Order By: Relevance
“…Similar results have been reported previously where an experimental evolution approach was used to investigate pathogen adaptation in completely unrelated environments such as mouse macrophage (Ensminger et al, 2012) and cystic fibrosis-like culture conditions in the presence and absence of fluoroquinolone antibiotics . In addition, unlike some other studies of the pathogen evolution in planta (Pitman et al, 2005;Lovell et al, 2009), our analysis did not detect the complete loss or gain of any gene among the bacterial strains compared with the parent.…”
contrasting
confidence: 48%
“…Similar results have been reported previously where an experimental evolution approach was used to investigate pathogen adaptation in completely unrelated environments such as mouse macrophage (Ensminger et al, 2012) and cystic fibrosis-like culture conditions in the presence and absence of fluoroquinolone antibiotics . In addition, unlike some other studies of the pathogen evolution in planta (Pitman et al, 2005;Lovell et al, 2009), our analysis did not detect the complete loss or gain of any gene among the bacterial strains compared with the parent.…”
contrasting
confidence: 48%
“…87 Moreover, it raises the question of whether other recombinases (e.g., those of ICEs, GIs, IS elements and transposons) are also affected by conjugation and regulated by LexA and the SOS response-certainly, stress affects P. syringae PPHGI-1 integrase expression. [58][59][60]88,89 Integrons have been found in a wide range of non-pathogenic and pathogenic bacteria in environments ranging from marine to terrestrial organisms and niches. 73,77,83,[90][91][92][93][94][95][96][97][98][99][100][101] Two types of integrons, the chromosomal integron (CI) and mobile integron (MI) have been identified: 70 CIs appear to represent a "core" gene capture system in Gram negative bacteria to enable genome flexibility for adaptation to diverse environments.…”
Section: Comparative Genomics Of Strains Of S Equi and S Zooepidemicusmentioning
confidence: 99%
“…78 Clearly, the host environment as well as the antibiotic treatment are likely to be influencing integron transfer on MGEs, a similar situation as seen with ICEs. 60 An interesting observation by van der Veen et al 102 was that the prevalence of integrons within the intestinal microbial populations decreased despite continued antibiotic treatment. This may indicate that there is a cost to the bacteria of carrying either the integron or its shuttle element.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pitman et al (2005) further demonstrated that the integrase gene xerC (PPHGI-1 ORF.100) is required for GI excision and that xerC transcriptional expression is greatly increased (50 times) in leaves undergoing the HR compared to in vitro conditions. Furthermore, Lovell et al (2009Lovell et al ( , 2011 demonstrated that PPHGI-1 can be transferred between strains of Pph via natural transformation and is able to integrate into the recipient strains chromosome.…”
Section: Introductionmentioning
confidence: 99%